2019
DOI: 10.3390/met9080861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Powder Preparation and Sintering Temperature on Properties of Spark Plasma Sintered Ti-48Al-2Cr-8Nb Alloy

Abstract: TiAl alloy has become a key element in aerospace and automotive engine development due to its favorable high temperature mechanical properties and low density. In this paper, high performance TiAl alloy was prepared using atomized Ti-48Al-2Cr-8Nb powder by spark plasma sintering. This paper analyzed the variation of density, microstructure, Vickers hardness, and fracture strength of TiAl alloys prepared with spherical pre-alloyed powder (named as SP powder) and pre-alloyed powder after 12 h of ball milling (na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Contrarily, the γ-phase exhibits excellent resistance to oxidation with low-level O and hydrogen absorption and poor ductility at room temperature (RT). In recent studies [51,52,93], TiAl powders were consolidated using SPS and the phases mentioned above were obtained. layer formation was achieved through avoiding mutual contact between the mold walls and the sample.…”
Section: Crystallographic Phasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrarily, the γ-phase exhibits excellent resistance to oxidation with low-level O and hydrogen absorption and poor ductility at room temperature (RT). In recent studies [51,52,93], TiAl powders were consolidated using SPS and the phases mentioned above were obtained. layer formation was achieved through avoiding mutual contact between the mold walls and the sample.…”
Section: Crystallographic Phasesmentioning
confidence: 99%
“…Combined A high performance Ti-48Al-2Cr-2Nb alloy was produced by employing SPS to consolidate spherical pre-alloyed (SP powder) and ball milled pre-alloyed powders (MP powder). In this work, Wang et al [93] carried out an analysis of the variations in density, microstructure and mechanical properties at different sintering temperatures. Similar phases as mentioned above (γ-TiAl, α 2 -Ti 3 Al) were achieved with additional TiAl 2 , TiAl 3 for both the SP and MP powders.…”
Section: Microstructures Of Tialmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, powder metallurgy technology [6], in particular spark plasma sintering (SPS), was adopted to prepare TiAl-based alloy parts. It was found that the full densification can be achieved at a relatively lower temperature by using pre-alloyed TiAl powders with small size and disorder structures [7]. Bulk nanostructured Ti-45Al-8Nb alloy with ultrahigh compressive strength can be obtained via SPS by using cryo-milled elemental powders [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods to generate metallic foams with improved apparent density distribution on the compact, such as cold compaction with double-effect machines, hot-pressing [32], or spark plasma sintering [36]. However, these techniques involve very high costs and specialized infrastructure compared to the conventional PM process.…”
Section: Introductionmentioning
confidence: 99%